Collaborative Learning tentang Perilaku School Bullying pada Anak Sekolah Dasar dengan Metode Learning Together di SDN Sawah III Kota Tangerang Selatan - Andi Prasetiyo; Marsha Adinda Wardani; Mutiara Permata Hati; Amanda Nariswari; Andika Juliansyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
students do collaborative learning about the behavior of School Bullying. This activity is carried out at SDN Sawah III, South Tangerang City. This writer uses dyad network theory. The method used is the Shared Learning Method by carrying out activities in the form of counseling, which are packaged in the form of interactive discussions, games and quizzes. with the aim of increasing knowledge and preventing bullying behavior. Bullying is a form of violence or rescue that is done intentionally by one person or group.